(Re)significando as experiências vividas: um olhar para a constituição identitária de professores de matemática, por meio das narrativas (auto)biográficas - Luz, Alexandra Garrote Angiolin (2022)
This study, of qualitative approach, used (auto)biographical narratives to investigate how mathematics teachers apprehend the different meanings attributed to the xperiences lived in their professional trajectory and how these experiences contribute to their rocess of identity constitution and reverberate in their teaching practices. The participants in this research are five mathematics teachers, from the São Paulo municipal education system, who work in 6th to 9th grade classes. The production of data was based on the proposal of the biographical project workshop, in which the (auto)biographical arratives - oral and written - and the reflections made by the reflective group integrate the corpus of analysis of this research. The biographical project workshop was held remotely due to the Covid-19 pandemic and included eight reflective meetings in which the participants produced, socialized, and reflected on the lived experiences that contributed to their professional identity constitution. To present the emotions, feelings, and subjectivities that emerged in the oral narratives, we chose to use transcription for data analysis. The lived experiences, narrated in the light of memory, the temporal dimension, and the affective dimension, revealed that the different socializations experienced (family, school, and professional), the identifications with the socially constructed attributions in relation to the profession, the continuing education focused on school, the affective relationship experienced in the teaching-learning process as students, and the relationship with the Other contributed significantly to the belonging in the professional identity constitution of each mathematics teacher. The results indicated that the (re)visit and reflection about the experiences lived through (auto)biographical narratives are powerful instruments to understand the process of identity constitution of mathematics teachers. The reflection around the lived experiences enabled the participants to constitute and reconstitute themselves, in a perspective of self-training, in a dialectical movement that links past, present and future